Prediction of flood event by using artificial neural network at Padas River - Amir Aliff, Amri (2015)
For the past few years, the flood that hits Beaufort District became worst with no early warning given out leaving citizens unprepared. Such warning is needed and can be achieved through modelling. In this study water level of Padas River is being used to produce a model by using Artificial Neural Network to predict the occurrence of flood from the rising of water level in Sungai Padas. Artificial Neural Network with feed forward back propagation architecture are used to produce a model to where future water level are produced by using past water level. The model that has been produced in this thesis proved to be practical in doing real time water level prediction as model 3-4000-6 has given satisfactory accuracy in forecasting. Therefore early warnings can be given to unaware citizens on the rising of water level that will surpass the danger level that will lead to flood.